Dreams of glory : the sources of apocalyptic terror - Fenn, Richard K. 1934- (Ashgate Pub, 2006)
Introduction : contemporary Christian Mullahs and their apocalypticism -- The apocalyptic vision as bad seed -- Radical preachers and Mullahs -- Terror and the apocalyptic imagination -- Apocalyptic visions as reaction to disaster -- The apocalyptic attack on the self -- Apocalyptic visions as ideology -- The test of time -- The theater and the courtroom -- Free association